2016
DOI: 10.7314/apjcp.2016.17.s3.77
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Levels of ErbB2 and CEA in Oral Squamous Cell Carcinoma Patients

Abstract: Oral squamous cell carcinoma (OSCC) is one of the ten most common causes of cancer death worldwide. Assessment of molecular changes can help detect and control lesions. The aim of this study was evaluation of salivary levels of ErbB2 and CEA in OSCC patients. In this case-control study, 27 OSCC patients and 26 healthy controls participated. After obtaining consent and filling out a questionnaire, unstimulated saliva samples were collected from people in the morning for measurement of the two markers using ELIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…In another study, immunoglobulins were detected at higher levels in OSCC patients as compared to controls and found to be involved in angiogenesis [60]. A similar observation was reported for several cell surface receptor glycoproteins, namely CD44, CD59 and CEA, which were found overexpressed in patients with OSCC [61]. Different zinc finger proteins were also found augmented in OSCC patients, namely ZNF510 [62] or Cyfra 21-1 and CK 19 [61][62][63].…”
Section: Oral Cancersupporting
confidence: 64%
“…In another study, immunoglobulins were detected at higher levels in OSCC patients as compared to controls and found to be involved in angiogenesis [60]. A similar observation was reported for several cell surface receptor glycoproteins, namely CD44, CD59 and CEA, which were found overexpressed in patients with OSCC [61]. Different zinc finger proteins were also found augmented in OSCC patients, namely ZNF510 [62] or Cyfra 21-1 and CK 19 [61][62][63].…”
Section: Oral Cancersupporting
confidence: 64%
“…Table 1 presents the descriptive characteristics of the 14 included studies in the meta-analysis. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] The different salivary biomarkers analyzed in different population groups (patients with OSCC, patients with oral potentially malignant disorders, and controls) are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies [13][14][15] analyzed the salivary levels of the carcinoembryonic antigen (CEA) in OSCC patients and controls. OSCC patients had higher levels of CEA with a statistically significant association (DM: 22.80, 95% CI: 5.46-40.14, P = 0.01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, different investigations mainly based on Western blot, or MRS-based targeted proteomics techniques have found cell-surface glycoproteins overexpressed in patients with OSCC such as CD44, CD59, or CEA. Other biomarkers related to the zinc finger protein family (ZNF) such as ZNF510, Cyfra 21-1, and CK19 have also been reported [ 153 155 ]. In this sense, Jou et al reported a sensitivity and specificity greater than 95% for salivary ZNF510 in the discrimination of tumors in early stages (T1 + T2) vs. advanced stages (T3 + T4) [ 156 ].…”
Section: The Salivary Proteome In the Health-illness Spectrummentioning
confidence: 99%